A Hands-Free Obstacle Detection and Avoidance System - Abdul-Niby, M.; Alameen, M.; Irscheid, O.; Baidoun, M.; Mourtada, H. (Engineering, Technology & Applied Science Research, 2015)
In this paper, we present a low cost hands-free detection and avoidance system designed to provide mobility assistance for visually impaired people. An ultrasonic sensor is attached to the jacket of the user and detects the obstacles in front. The information obtained is transferred to the user through audio messages and also by a vibration. The range of the detection is user-defined. A text-to-speech module is employed for the voice signal. The proposed obstacle avoidance device is cost effective, easy to use and easily upgraded.